Estimating Foreign Exchange Reserve Adequacy - Hakim, Abdul (Universitas Prasetiya Mulya, 2013)
Accumulating foreign exchange reserves, despite their cost and their impacts on other macroeconomics variables, provides some benefits. This paper models such foreign exchange reserves. To measure the adequacy of foreign exchange reserves for import, it uses total reserves-to-import ratio (TRM). The chosen independent variables are gross domestic product growth, exchange rates, opportunity cost, and a dummy variable separating the pre and post 1997 Asian financial crisis. To estimate the risky TRM value, this paper uses conditional Value-at-Risk (VaR), with the help of Glosten-Jagannathan-Runkle (GJR) model to estimate the conditional volatility. The results suggest that all independent variables significantly influence TRM. They also suggest that the short and long run volatilities are evident, with the additional evidence of asymmetric effects of negative and positive past shocks. The VaR, which are calculated assuming both normal and distributions, provide similar results, namely violations in 2005 and 2008.